Antenatal care implementation between two asian countries: A study from Indonesia and Taiwan - Pradana Putri, Anggie; Ying Lu, Yu; Yu Lai, Chien; Ru Rong, Jiin; Ying Lee, Tzu; Hanifah, Lilik (Jurnal Kebidanan Indonesia, 2024)
Background: Antenatal care (ANC) is essential for safeguarding the health of both mothers and their unborn children troughout pregnancy. Understanding the differences from other county provides valuable insight for enhancing maternal and neonatal health outcomes in various healthcare environments. Aims: This study compares the implementation of ANC between Indonesia and Taiwan. Method: A qualitative approach was used to explore ANC implementation between Indonesia and Taiwan. Participants were recruited using purposive sampling, consisting of 6 healthcare providers, 10 pregnant women, and 3 experts from Taiwan and Indonesia. Data were collected through interview, focused group discussions, and document review. Collaizi’s strategy was used to analyze the data. To ensure the trustworthiness of the study, credibility, transferability, dependability, and confirmability were encouraged. Result: There are three themes emerged from this study with twleve following sub-themes. The themes are institutional and structural framework of ANC, ANC education and awareness, and self-empowerment and encourage of pregnant women. Conclusion: By adopting best practices from Taiwan, Indonesia can enhance its ANC services and empower pregnant women, leading to improved maternal and neonatal health outcomes.